COVID-19パンデミック下における精神看護専門看護師による看護師支援のプロセス - 福田 紀子; 野末 聖香; 田久保 美千代; 平岩 千明 (日本看護科学会誌, 2023)
要旨　目的：COVID-19パンデミック下における精神看護専門看護師（精神看護CNS）による看護師支援のプロセスを明らかにする．　方法：17名の精神看護CNSへの半構成的インタビューを行い，グラウンデッド・セオリー・アプローチによる分析を行った．　結果：精神看護CNSによる看護師支援は，【危機状況下で最善のケアを提供するための看護師支援】をコアカテゴリーとする9つのカテゴリーから形作られた．看護師のメンタルヘルスに関わる状況を把握し，多職種や看護管理者と協働し，看護師が安心して患者・家族ケアを行える環境を整え，危機状況下でも患者・家族に最善のケアを提供できるよう看護師を支援していた．　結論：精神看護CNSによる多職種や管理者と連携した支援は，看護師のレジリエンスを高める可能性が示唆され，支援の独自性は，患者・家族ケアをともに行うことを通して看護師を支援することであった． 　Objectives: This study aimed to clarify the process of support for nurses provided by Certified Nurse Specialists (CNS) in Psychiatric Mental Health Nursing during the COVID-19 pandemic.　Methods: Data from semi-structured interviews with 17 CNSs were analyzed using a grounded theory approach.　Results: The process of support for nurses consisted of nine categories, with the core category of "Supporting nurses to provide the best patient and family care under the crisis." The CNSs grasped the situation related to the mental health of nurses and collaborated with multi-disciplinary professionals and managers to create a supportive environment where nurses could feel secure and sought out nursing care for patients and families with nurses in the adversity caused by the pandemic.　Conclusion: The support provided by the CNSs in collaboration with other professionals and managers contributed to the resilience of the nurses. The uniqueness of the support was to assist the nurses by working together to provide patient and family care, which was made more difficult by the pandemic.